Dynamic sliding mode control based on dynamic switching functions and upper bound for the mass – spring – damper - Phạm Thanh Tùng; Lê Hữu Toàn; Nguyễn Chí Ngôn (Journal of Military Science and Technology, 2022)
This research proposes a dynamic sliding mode control based on dynamic switching functions and upper bound (DSMC-DSF-UB) for the mass – spring – damper system with disturbance. The time derivative of the control input of the dynamic sliding mode controller (DSMC) is treated as a new control variable for the augmented system which is composed of the original system and the integrator. This DSMC can transfer discontinuous terms to the first-order derivative of the control input. Therefore, the proposed controller effectively reduces the chattering phenomenon in the traditional sliding mode control. Simulation results in MATLAB/Simulink are compared with PID controller to demonstrate the effectiveness of the proposed method with the rising time achieves 0.443(s), the settling time is 0.7292(s), the overshoot is about 0.0089(%) and the steady – state error converges to 0.